THE Effectiveness of the Conditioning by Unit III of the State Security Intelligence Unit in Preventing Conflicts Between Silat Organizations in the Gresik Police Jurisdiction - Pribadi, Dikstra Andika Brahmana (Advances in Police Science Research Journal, 2024)
This research is motivated by the very frequent phenomenon of conflict between pencak silat schools in the jurisdiction of the Gresik Police. This conflict resulted in a lot of loss of both property and lives. Therefore, in an effort to create a conducive security and social security situation, it is necessary to prevent conflict between pencak silat schools through effective fundraising efforts carried out by the Gresik Police Satintelkam. The analytical knife in this research uses theories and concepts, including: fishbone diagrams, organization and management theory, basic intelligence concepts, fundraising concepts. The research approach used is qualitative with field research methods. Sources of information are obtained from primary data sources and secondary sources. The data collection techniques are by conducting interviews, observation and document study. Data analysis was carried out using techniques, namely data reduction, data presentation and drawing conclusions. Based on the research findings and analysis carried out, the results obtained were that fundraising activities were still lacking so that conflict prevention between silat schools was not optimal. Therefore, it requires the support of management elements so that information can be processed according to the needs of leaders in making decisions to prevent social conflict. Handling social conflicts between pencak silat schools is carried out by all functions of the Gresik Police in an integrated manner. Discussion so that the author can conclude that handling social conflict by the Gresik Police is carried out through direct communication. The effectiveness of organizing Satintelkam to prevent conflicts between pencak silat schools can be effective through optimizing management elements. The first suggestion is to propose to the leadership to improve the human resources of Satintelkam members in the campaign. Second, it is necessary make silat organization community to solve conflict.